2007
DOI: 10.1292/jvms.69.1109
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of the Testicle and Sex Accessory Glands Following the Administration of Boldenone and Boldione as Growth Promoters in Veal Calves

Abstract: ABSTRACT. Boldenone and its precursor Boldione are illegally used for anabolic purposes in humans, horses and cattle. To develop more effective policies and programs to maximize food security, Italian Public Health Services investigate all indicators capable of assisting the recognition of treated animals, and prioritize research and the formulation of action strategies for the promotion of healthy eating. Thus, an experimental administration of boldenone and boldione at anabolic dosages in veal calves was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
5
18
2
Order By: Relevance
“…Similar results have been reported in horses (Maher et al. 1983), in female rats (Howe & Morello 1985) and in veal calves (Cannizzo et al. 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results have been reported in horses (Maher et al. 1983), in female rats (Howe & Morello 1985) and in veal calves (Cannizzo et al. 2007).…”
Section: Discussionsupporting
confidence: 89%
“…There have been relatively few studies which have investigated the detrimental effects of BOL administration on male function. These have explored their role as growth promotors on testis; bulbourethral glands and prostates of veal calves (Groot & Biolatti 2004; Cannizzo et al. 2007), on reproductive function of stallions (Squires et al.…”
mentioning
confidence: 99%
“…Boldenone (1,4-androstadiene-17β-ol-3-one; BOL) is an androgenic steroid that improves the growth and food conversion in food producing animals. In most countries worldwide, this anabolic steroid is forbidden for meat production (Kuhn, 2002;Cannizzo et al, 2007;Soma et al, 2007). They were developed mainly for veterinary use, mostly for horse treatment and well known under the trade names Equipoise, Ganabol, Equigan and Ultragan.…”
Section: Introductionmentioning
confidence: 99%
“…However, illegal substances used in livestock cause the occurrence of alterations, to different extents, in organs that respond to their stimulating or inhibiting effects [1]. Indeed, over the years, studies on this topic have suggested that the use of growth promoters can be highlighted by both macroscopic and histological changes of the genital tract organs and sex accessory glands, in both males and females [6,23,24,32], or other organs such as the thymus [7,28] or thyroid [37]. These lesions persist long enough to be detected at slaughter.…”
mentioning
confidence: 99%